PENGAWASAN AKTIVITAS KAPAL PENANGKAPAN IKAN DI PANGKALAN PENGAWASAN SUMBER DAYA KELAUTAN DAN PERIKANAN KOTA BATAM - Purba, Cindy; Epriadi, Dedi (SCIENTIA JOURNAL, 2022)
The sea-surrounded Batam area has the potential for Marine and Fisheries resources. The activity of large fishing vessels is observed along the city’s sea of Batam. PSDKP Batam city is under the KKP (Ministry of Marine Affairs and Fisheries) which oversees the resources and fisheries available in Batam. The purpose of this research is to know the role of PSDKP in overseeing fishing operations in Batam, The method used in this research is a qualitative descriptive method. The data-collection techniques used in this research include interviews, observation and documentation. The results of this research show that the control conducted by PSDKP is still lacking due to some factors, the lack of personnel and limited budget owned by PSDKP. There are still fishing vessels that have incomplete documents. The things PSDKP need to do are improving the number of qualified fisheries supervisors for better supervision of fishing vessels, maintaining good coordination with those involved in supervision of fishing vessels, and proposing an additional budget to get extra patrol boats. Keywords: Supervision , Fishing Vessel Activity, PSDKP Batam